Canadian History Post-Confederation - Belshaw, John Douglas (Open textbook library., 2016)
This textbook introduces aspects of the history of Canada since Confederation. “Canada” in this context includes Newfoundland and all the other parts that come to be aggregated into the Dominion after 1867. Much of this text follows thematic lines. Each chapter moves chronologically but with alternative narratives in mind. What Aboriginal accounts must we place in the foreground? Which structures (economic or social) determine the range of choices available to human agents of history? What environmental questions need to be raised to gain a more complete understanding of choices made in the past and their ramifications?